Behavioral Therapy Implementation through Token Economy to Increase Activity of Daily Living (ADL) Productivity in RSKD Duren Sawit Client "F" with Schizophrenia : Penerapan Behavioral Therapy melalui Token Economy untuk Meningkatkan Produktivitas Activity Of Daily Living (ADL) pada klien “F” Skizofrenia di RSKD Duren Sawit - Dhepita Septiyani; Nazera Nur Utami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Schizophrenia is a chronic mental disorder that significantly impacts an individual's social functioning and daily productivity. This study aims to analyze the effectiveness of improving the productivity of Activity of Daily Living of schizophrenic clients with a behavioral therapy approach through Token Economy. The case study was conducted on a 35-year-old female client "F" with a diagnosis of schizophrenia F20.0 at the Duren Sawit Regional Special Hospital. The method used was casework with observation, interview, and documentation study techniques. The results of the intervention showed that the implementation of the intervention through Token Economy consistently succeeded in changing the client's behavior, the client's participation and independence were proven to increase with the achievement of 405 of the 420 target points. In addition, the client's medication adherence was also consistently maintained throughout the intervention period. The social work intervention carried out by the practitioner with the support of client "F"'s family played an important role in the psychosocial rehabilitation of schizophrenic clients. The intervention showed that the behavioral therapy approach through Token Economy can improve the client's daily productivity.